2015
DOI: 10.1097/j.pain.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and electrophysiological abnormalities in two rat models of antiretroviral drug-induced neuropathy

Abstract: Painful peripheral neuropathy due to the antiretroviral therapy used to treat HIV is one of the most prevalent side effects occurring in at least 30% of patients living with this infection. We have evaluated the electrophysiological and behavioral effects of d4T and ddC on peripheral large and small nerve fibers in male rats treated with d4T (Sprague-Dawley, 50 mg/kg, twice within 1 week), ddC (Wistar, 50 mg/kg, 3 times per week for 3 weeks), or vehicle. The effect of the interventions was assessed using behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Amplitude and NCV of sensory nerve action potential (SNAP) and compound muscle action potential (CMAP) were recorded as previously described (Garcia‐Perez et al., ). Briefly, NCV was recorded from the tail using conventional clinical‐grade equipment (Medelec Synergy N2 EMG System, Viasys Healthcare, Madison, USA) employing recording and stimulating stainless steel needle electrodes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplitude and NCV of sensory nerve action potential (SNAP) and compound muscle action potential (CMAP) were recorded as previously described (Garcia‐Perez et al., ). Briefly, NCV was recorded from the tail using conventional clinical‐grade equipment (Medelec Synergy N2 EMG System, Viasys Healthcare, Madison, USA) employing recording and stimulating stainless steel needle electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated that microneurography has been successfully employed to reveal neural characteristics of C‐nociceptors’ activity in patients and animal models of neuropathic pain (Serra et al., , , ; Garcia‐Perez et al., ). Moreover, recording of spontaneous discharges in different types of C‐fibres identified by a latency‐based marking method has become an important tool to identify abnormalities in neural traffic of C‐nociceptors.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that this was due to spironolactone, the antiandrogen she had taken for 15 years, which also has proandrogenic activity. 86 Another case report described a transgender man with hypokalemic thyrotoxic periodic paralysis exacerbated by testosterone therapy, suggesting that the androgenic effect of testosterone on the Na þ/K þ -ATPase pumps contributed to hypokalemia and requiring this patient to stop taking GAHT. 87…”
Section: Neuromuscular Disordersmentioning
confidence: 99%
“…This group includes medications zidovudine or azidothymidine, didanosine, zalcitabine (ddC), stavudine (d4T), lamivudine, and abacavir. ddC was one of the first HIV/AIDS‐approved antiretrovirals and is now considered to be the most neurotoxic (Garcia‐Perez, Solà, Sumalla, & Serra, 2015) The introduction of combination antiretroviral therapy (cART) dramatically reduced the morbidity and mortality associated with HIV among patients who have access to treatment. (Mwesiga, Kaddumukasa, Mugenyi, & Nakasujja, 2019).…”
Section: Introductionmentioning
confidence: 99%